PENGEMBANGAN MODEL PEMBELAJARAN HOMESCHOOLING UNTUK MENINGKATKAN MINAT BELAJAR SIWA DI SIBOLGA ILIR - Darwis, Darwis; Syaputra, Adi; Amri, Khairul (Universitas Muhammadiyah Tapanuli Selatan, 2024)
The research aims to develop a homeschooling learning model for students in Sibolga Ilir. Homeschooling learning is carried out on students in groups in community homes to learn together and increase students' interest in learning to the maximum. The problem in this study is that the learning interest of students in Sibolga Ilir Village is not good. The research method develops a homeschooling learning model for students according to their learning interests. Overcoming this problem is carried out with a homeschooling learning model by grouping according to students' talents and learning interests. The results of the study of students' learning interests are good for each learning group with the homeschooling learning model in Sibolga Ilir village. Homeschooling learning can foster better sensitivity to social feelings towards peers. Able to provide empathy and quickly understand the feelings of others. Homeschooling learning activities will increase students' interest in learning even better.